Optimizing the Application of International Classification Standards of Function, Disability & Health (ICF) Cases Musculosceletal Disorders in Employees Permata Hospital Bekasi - Indasah; Surahman Sukron Rosyadi; Dwi Dimas; Muammar (Journal of Community Engagement in Health, 2024)
Optimal health services are an absolute requirement for government administrators and private parties. Optimizing health services can be done through innovation, to bring services closer to the community, more easily accessible, higher quality and cheaper. The application of innovation is expected to make communication between medical personnel better, each individual is encouraged to work more quickly, precisely and carefully, and innovation is expected to give birth to a better work culture. The direct service to the community that is quite highlighted is health services. On this basis, we carry out service interventions in the form of workshops and mentoring for PERMATA BEKASI Hospital employees to further optimize service innovation. The workshops carried out included the latest ICF (Japan) international standard assessment system that can be applied in Indonesian health services, Optimizing Employees in preventing Musculosceletal disorder problems and Implementing and optimizing the addition of Dry needle services for Musculosceletal disorder cases. The activity was carried out on June 29 2024. Before conducting the workshop, service innovations that had been implemented were identified. As a result, the residency, which previously had been appealed to several international hospitals, including Japan and Thailand, is still in the process of standardization efforts carried out by countries whose index of health services or hospitals can be an example and motivation.